COEXISTING KRAS AND NRAS MUTATIONS IN CAECAL ADENOCARCINOMA AND CONTIGUOUS ADENOMA – A CASE REPORT. (February 2015) - Vagaja, Nina; Parry, Jeremy; McCallum, Dugald; Bentel, Jacqueline
Abstract : Aim: Activating mutations of KRAS and NRAS, isoforms of RAS proto-oncogenes which influence cell proliferation, differentiation and survival, arise in 35–40% of colorectal carcinoma (CRC), and are in recent years proven to convey resistance to anti-EGFR monoclonal antibody therapy in metastatic CRC. These mutations in CRCs are considered mutually exclusive through redundancy. Here we report and characterise a case of caecal CRC with coexisting KRAS and NRAS mutations. Methods: An 81-year-old male, presenting with fever and right iliac fossa pain, underwent right hemicolectomy after CT diagnosis of 43 mm caecal mass. Tissue sections and immunohistochemical expression of CK7, CK20, CDX2, MSH2, MSH6, MLH1 and PMS2 were examined by two pathologists. Mutation analysis of KRAS, NRAS and BRAF was performed on lesional DNA using bidirectional Sanger sequencing of amplified PCR product. Results: Low-grade CRC (T2N0MX) and contiguous sessile high-grade tubulovillous adenoma, both CDX2 +, CK20 + and CK7 –, were identified. Both lesions contained KRAS c.35G > T (G12 V) and NRAS c.34G > A (G12S) mutations, without immunohistochemical evidence of microsatellite instability. Conclusion: We report, for the first time, coexisting KRAS and NRAS mutations in a single CRC. This may have therapeutic significance. Current understanding of RAS proto-oncogenes in pathogenesis and treatment response in CRCs is discussed.